Interaction of Coumarin, Daphnetin, Fraxetin from Natural Materials with Carbanoic anhydrase II in Inhibiting Glaucoma - Rismi Verawati; Fajri Ikhsan; Okta Suryani (Universitas Nusa Bangsa, 2024)
This article explores the interaction of Coumarin compounds and their derivatives obtained from natural extracts with Carbonic anhydrase II protein in inhibiting Glaucoma computationally. This research method includes modeling using software such as Pymol, Pyrx, Protein Plus, and Lipinski Rule of Five. The results showed Binding Affinity and RMSD of Coumarin, Daphnetin, and Fraxetin compounds with Carbonic anhydrase II with strong interaction. Protein Plus analysis was used to visualize the interaction that occurred between the compound and the Carbonic anhydrase II protein, in addition to the Lipinski Rule of Five test results, which showed results that were in accordance with the rules and met the drug criteria. These results indicate that Coumarin, Daphnetin, and Fraxetin compounds as Carbonic anhydrase II inhibitors have the potential to inhibit glaucoma. Daphnetin compound is the best inhibitor seen from the Binding Affinity value of -6.9, -5.8, and -5.5, as well as the results of Daphnetin's Lipinski Rule of Five data. However, further research is needed to validate this computational study.